On Symmetric Strictly non-Volterra Quadratic Stochastic Operators - Jamilov, U.U. (Discontinuity, Nonlinearity, and Complexity, 2026)
For a symmetric strictly non-Volterra quadratic stochastic operator on the three-dimensional simplex it is proved that this operator has a unique fixed point. A sufficient condition of attractiveness for the unique fixed point is found. For such operators we describe the set of ω− limit points. We proved that some classes of such operators have infinitely many periodic points. Also it is shown that there are trajectories which are asymptotically cyclic with period two.